Primary HPV-based cervical cancer screening in Europe: implementation status, challenges, and future plans - Maver, P J; Poljak, M (Clinical microbiology and infection, 2020)
Cytology-based screening has been a cornerstone of cervical cancer prevention for decades. Following extensive evidence demonstrating higher sensitivity and accuracy, lower variability and better reproducibility of human papillomavirus (HPV)-based screening compared with conventional or liquid-based cytology, recent European guidelines strongly recommend primary HPV-based screening over standard cytology-based screening. In addition, HPV-based screening offers the possibility of self-sampling and makes possible longer screening intervals in women with negative screening results. We summarize the current status of implementation of HPV-based screening in Europe, describe the real-life experience and challenges from countries already performing HPV-based screening, and briefly review immediate and long-term plans for screening implementation in selected European countries. Data were obtained from peer-reviewed literature, personal communication with experts and authorities involved in formulating national recommendations and practical guidelines, and relevant national websites. As of July 2019, the Netherlands and Turkey are the only European countries with fully implemented national HPV-based cervical cancer screening. Italy, Sweden and Finland have already implemented HPV-based screening in several regions, and several other countries are at various stages of implementation. Some countries are considering transitioning from cytology-based to HPV-based screening, but are struggling with the suboptimal performance of current population-based programmes. Implementation of HPV-based screening has resulted in higher colposcopy referral rates, but also higher detection rates of CIN3+ lesions and cervical cancers requiring immediate treatment. Cytology is mostly used as a triage test, although other strategies are under consideration in some countries. HPV-based screening is best suited in organized population-based screening settings. In 2019, cervical cancer screening policies across Europe vary greatly. Experience in countries with national and regional HPV-based screening already implemented is generally very positive. Urgent action is needed in many European countries, especially those with suboptimal opportunistic cytology-based cervical cancer screening.